2014
DOI: 10.18542/ragros.v6i1.1845
|View full text |Cite
|
Sign up to set email alerts
|

CULTIVO DE TOMATE (Solanum lycopersicum) HIDROPÔNICO SOB DIFERENTES NÍVEIS DE FÓSFORO E POTÁSSIO EM SOLUÇÃO NUTRITIVA

Abstract: RESUMO:O tomate está entre as hortaliças mais consumidas no mundo, sua produção anual no Brasil é estimada em torno de quatro milhões de toneladas. O objetivo do trabalho foi estudar o efeito de diferentes doses de fósforo e potássio no crescimento de tomateiro, cultivado em sistema hidropônico. O trabalho foi conduzido em casa de vegetação do Instituto de Ciências Agrárias da Universidade Federal Rural da Amazônia, no período de outubro de 2008 a janeiro de 2009, em solução nutritiva. O delineamento experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…This aspect is particularly relevant to horticulture because most producers have a small growing area in which they seek to obtain the maximum possible income (RINALDI et al, 2008). Soilless crops allow production in a small area and can maintain product quality at satisfactory levels, as well as serving as a strategy for soil conservation and preservation of water sources (OLIVEIRA et al, 2014, OLIVEIRA et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect is particularly relevant to horticulture because most producers have a small growing area in which they seek to obtain the maximum possible income (RINALDI et al, 2008). Soilless crops allow production in a small area and can maintain product quality at satisfactory levels, as well as serving as a strategy for soil conservation and preservation of water sources (OLIVEIRA et al, 2014, OLIVEIRA et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The formulations of the nutrient solutions used in the hydroponic production of plants are of great interest. Several formulations of nutrient solution are proposed in the specialized literature, however, it is necessary to determine the effects of solution concentration and nutrient ratios on plant growth, plant development, production, and fruit quality (FERNANDES; MARTINEZ; OLIVEIRA, 2002;MELO et al, 2014;DINIZ et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate satisfactory results in the cultivation of plants in the DFT system, for tomato crops (Melo et al, 2014), of the coriander (Silva et al, 2016) and lettuce (Viana et al, 2018). However, some authors such as Bione et al (2014) and Maia et al (2017) observed that there is no compendium of consolidated information on the hydroponic cultivation of this culture under saline stress for basil.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the responses varied in accordance with the soil type and soil P availability. The application of phosphorus showed a significantly positive effect in tomato yield (Melo et al, 2014), but the effects of P on seedling production are still unknown. Nishimoto et al (1977) observed that P contents in tomato leaves ranged from 3.0 to 5.0 g/kg, when reaching their maximum yield of 95%.…”
Section: Introductionmentioning
confidence: 99%